Analysis of government policy on the development and empowerment of MSMEs through the lens of latest literature - Kartani; Hayat; Suyeno (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2024)
This article explores the implementation of public policies regarding Micro, Small, and Medium Enterprises (MSMEs) with a focus on government collaboration with MSME stakeholders, mentoring programs, poverty alleviation, implementation effectiveness, and policy recommendations. The analysis encompasses several related studies that highlight government efforts to enhance community welfare through MSME development. Collaboration and synergy between the government and MSME stakeholders form the foundation of policies, emphasizing the significance of this collaboration in improving the economic conditions of MSME stakeholders. Additionally, MSME mentoring programs by the government become crucial elements to ensure sustainable development, although further improvements are needed. Efforts to alleviate poverty through MSME empowerment underscore the need for careful consideration of the strengths and strategies of actors involved in policy implementation. Evaluates the effectiveness and suitability of policy implementation, highlighting the importance of effective communication and optimal coordination in policy execution. Policy recommendations involve consistent budget allocation for MSMEs, bureaucracy acceleration, and broader collaboration with the private sector. This analysis demonstrates the complexity of public policy implementation for MSMEs and emphasizes the need for concrete steps to enhance its effectiveness.